Bacteria and their cell wall components uniformly co-activate interleukin-17-producing thymocytes. (7th November 2014) - Weber, A; Zimmermann, C; Kieseier, B C; Hartung, H-P; Hofstetter, H H
Summary: Interleukin (IL)-17-producing T cells play a critical role in the immune response against microbial pathogens. Traditionally, experimental studies have focused upon understanding the activity of IL-17-producing T cells which differentiate from naive T cells in the peripheral immune system. However, we have demonstrated previously that IL-17-producing T cells are also present in the thymus of naive wild-type mice and can be co-activated there by microbial stimuli. Other studies have supported the concept that IL-17-producing thymocytes have a specific role in the immediate defence against microbial pathogens, which is independent from the development of an adaptive immune response. Given an important role of the thymus in systemic bacterial infection and sepsis, in this study we investigate the effect of a broad spectrum of bacteria and cell wall components on thymocyte cytokine production. Surprisingly, we find that all types of bacteria investigated (including non-pathogenic species) uniformly activate IL-17-producing thymocytes upon α-CD3 stimulation. In contrast, there is a heterogeneous effect on IL-6 and interferon (IFN)-γ-production with Gram-negative bacteria inducing far higher frequencies of IL-6- and IFN-γ-producing thymocytes than Gram-positive bacteria. We conclude that IL-17-producing thymocytes constitute a 'first line of recognition', but not a 'first line of defence' against bacteria in general. Their activity might lead to immune activation, but not necessarily to a pathological inflammatory disease condition. The difference between these two states might be determined by other immunological effector molecules, such as IL-6 and IFN-γ.